Elicitation of preferences in the second half of the shared decision making process needs attention; a qualitative study - Savelberg, W.; Smidt, M.; Boersma, L. J.; van der Weijden, T. (BMC health services research, 2020)
It is known that the use of a Patient Decision Aid (PtDA), combined with advice for professionals on how and when to use it, can enhance the involvement of patients in the treatment decision. However, we need more knowledge with respect to the intention-behaviour gap. This study aims to analyse patients' experiences with the Shared Decision Making (SDM) process to find clues to close this gap. This qualitative study was part of a pilot study aiming to implement SDM in early adopter breast cancer teams. Patients were given access to a personalised PtDA. Breast cancer teams were instructed on how and when to deliver the PtDA. We interviewed 20 patients about their experience with the PtDA and SDM in general. Most patients experienced SDM, though to a certain extent. Choice talk and option talk were commonly experienced, however the elicitation of preferences and decision talk was rare. The PtDA was used by the majority of patients (N = 13), all indicating that it was useful, especially to recall all the information given. Patients appreciated the contribution of breast cancer nurses in the SDM process. They considered them as true case managers, easy to approach and supportive. Although patients felt well-informed and satisfied about risk-communication, the elicitation of preferences appeared very limited to non-existent. We recommend that breast cancer teams divide tasks in the SDM process and reallocate the elicitation of preferences to the nurses in a well-defined clinical pathway.